Clay nanoparticles : properties and applications - Cavallaro, Giuseppe; Fakhrullin, Rawil; Pasbakhsh, Pooria (Micro & nano technologies., 2020)
Clay Nanoparticles: Properties and Applications sets out the major properties of clay nanoparticles and their technological applications. The first part of the book focuses on the characterization of nanoclays, including layered, fibrous and tubular clay minerals. The second part illustrates the current and potential applications of nanoclays within material science and biotechnology. These include the development of geopolymers and bionanocomposites based on sustainable polymers filled with ecocompatible nanoclay. The potential use of nanoclays as flame retardants is also discussed, along with the correlation between the properties and potential applications of several nanoclay types.